2017
DOI: 10.1186/s12889-017-4032-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a vaccine scare on parental views, trust and information needs: a qualitative study in Sydney, Australia

Abstract: BackgroundVaccine safety scares can undermine public confidence in vaccines and decrease immunisation rates. Understanding and addressing parental concerns arising during such scares can assist in lessening their impact. In Australia in April 2010 there was a temporary suspension of influenza vaccine for children under 5 years of age after reports of an increase in the rate of adverse events following vaccination. This qualitative study aimed to explore the impact of the vaccine suspension on parental knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 42 publications
2
28
0
Order By: Relevance
“…This unsupported research leaves some higher‐SES parents feeling qualified to interpret results; autonomy in health decision‐making was synergistic with postmodern ideals and healthism beliefs . Conversely, an Australian study on the impact of vaccine scares on parental views found simply “a need for information which is easily found, transparently authored, well‐referenced, and written in a way that is easily understood” …”
Section: Introductionmentioning
confidence: 99%
“…This unsupported research leaves some higher‐SES parents feeling qualified to interpret results; autonomy in health decision‐making was synergistic with postmodern ideals and healthism beliefs . Conversely, an Australian study on the impact of vaccine scares on parental views found simply “a need for information which is easily found, transparently authored, well‐referenced, and written in a way that is easily understood” …”
Section: Introductionmentioning
confidence: 99%
“…[13,42] The implications of a recommended but non-funded vaccine are well documented, with increased parental support for vaccines included on the NIP. [42,43] This is also true of providers, with enhanced support for government funded vaccines and lower perceptions of disease severity towards non-funded vaccines previously noted. [32] Government funding implies to parents and providers alike that the vaccine is a priority, thereby influencing the decision-making process.…”
Section: Community Awareness Of Influenza Vaccinementioning
confidence: 89%
“…Concerns about vaccine safety has remained a barrier to influenza vaccination in children complicated by the serious adverse events in 2010. [43,44] Yet even prior to this, parental belief in the vaccine's safety was shown to be associated with support for vaccination. [42] More recent studies have also found belief in the vaccine's safety to be positively associated with vaccine uptake [12] but also suggest that negative publicity has lingered, complicated by parental knowledge towards the vaccine itself with a perception that the vaccine has not been around long enough, qualified by ensuring the safety of the vaccine.…”
Section: Parental Vaccine Concernsmentioning
confidence: 99%
“…Moreover, vaccine may be imperfect in the sense that (i) there can exist unwanted, adverse side effects of various degrees, albeit being minor most of the time, causing exaggerated perceived risk or cost of vaccination [8,9,32], and (ii) vaccination only can confer partial protection against the disease [33][34][35], also known as primary and secondary vaccine failures [36][37][38]. Indeed, the presence of imperfect vaccine can diminish public confidence in vaccine and thus erode an individual's intention to vaccinate [39][40][41][42][43][44]. Although the efficacy and cost-effectiveness of vaccination has been a topic of extensive investigation [45 -52], the complications of imperfect vaccine on uptake behaviour have not been fully understood yet [39,40,42,43,53,54].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the presence of imperfect vaccine can diminish public confidence in vaccine and thus erode an individual's intention to vaccinate [39][40][41][42][43][44]. Although the efficacy and cost-effectiveness of vaccination has been a topic of extensive investigation [45 -52], the complications of imperfect vaccine on uptake behaviour have not been fully understood yet [39,40,42,43,53,54].…”
Section: Introductionmentioning
confidence: 99%